Pengembangan Garis Ajaib untuk Meningkatkan Prestasi Belajar Bilangan Bulat Siswa Sekolah Dasar - Wulandari, Tanti Ratna (Jurnal Didaktika Pendidikan Dasar, 2020)
Mathematics grade VI achievement in Wates SDN integer material is still disappointing. This is indicated by the low student achievement. The results of problem identification are the factors of the media’s lack of interest in learning. For this reason, the writer makes a media that is expected to help understanding in learning. The media are named magic lines. The purpose of the report is to provide an overview of the process of making, the learning process, and student achievement after the development of the magic line. In the process of creating this magic line media the authors develop it with the concept of R & D, namely research and development. During the learning process students look active and enthusiastic. This shows that learning with magic line media can increase student involvement in learning. The results of data analysts showed a significant improvement in the aspects of knowledge and skills. KKM aspects of knowledge and skills have increased to 80% from 60%. The mean knowledge of 65.2 rose to 78.2. The aspect of average skill before 67.6 rose to 80.8. Thus it can be concluded that the magic line media is able to increase student learning achievement.